Do Rheumatoid Arthritis Patients Rate their Health Status Different than their Caregivers? - Bahlas, Sami; Fathaldin, Omar; Janoudi, Nahid; Almoallim, Hani; Ibrahim, Ashraf; Algohary, Shereen (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2015)
Objective: To compare the ratings given by the caregivers regarding the health status of their rheumatoid arthritis (RA) patients to those recorded by the patients themselves and to assess the effect of caring for a patient with RA on the mental health of the caregiver. Methods: This is a non-interventional, cross-sectional, multi-center epidemiological study conducted at the outpatient clinics of two hospitals in Saudi Arabia. The patients included were diagnosed with RA, over 18 years of age with 1-5 years of disease duration, and all had an identifiable single caregiver who was willing to participate in the study. Results: 40 patients of whom 92.5% were women and the mean age of 44.6 years. The mean visual analogue scale (VAS) score was 4.98 for general health. The mean Health Assessment Questionnaire (HAQ) for the patients according to themselves was 1.31 (±0.68), while that stated by caregivers was 1.40 (±0.69); thus, the mean scores given by the caregivers was 0.091 points higher than that provided by the patients themselves (95% confidence interval [CI], 0.167–0.014) (p=0.0214). Further, 43% of the caregivers gave higher HAQ scores to their related patients than the patients themselves, while 30% gave similar HAQ scores. The caregivers scored a mean of 21 points in the Zarit Burden Interview (±12.1), with 47.5% reporting mild to moderate burden, and 5% reporting moderate to severe burden. Conclusion: RA patients showed a tendency to understate their disease burden and as compared to that observed by caregivers who suffer from considerable level of burden.
Keywords: disease burden